Spectrophotometric determination of mosapride in pure and pharmaceutical preparations - Revanasiddappa, Hosakere Doddarevanna; Veena, M. A. (Eclética Química, 2007)
Two simple and sensitive spectrophotometric methods (M 1 and M 2 ) for the determination of mosapride in pure and in pharmaceutical preparations are described. These methods are based on the interaction of diazotized mosapride (MSP) couples with chromotropic acid (CTA) [M 1 ] in alkaline medium and diphenylamine (DPA) [M 2 ] in acidic medium. The resulting azo-dyes exhibit maximum absorption at 560 nm and at 540 nm for methods M 1 and M 2 , respectively. All variables were studied in order to optimize the reaction conditions. No interferences were observed from excipients, and the validity of the each method was tested against reference method.